Intimate Partner Violence: An Inaudible Sound - Alizah Alaman; Munira Minaz Ali (International Journal on Women Empowerment, 2016)
Intimate partner violence (IPV) is defined as a behavior in an intimate relationship that determines physical, emotional or sexual harms including physical aggression, sexual coercion, psychological abuse and other controlling behaviors on women by her intimate partner. This dreadful violence is pervasive in both low and high income countries and mostly encountered by female population. Likewise, Pakistan is one of the low-income countries where 57.6% women suffer from physical abuse by their intimate partners. Mostly this violence is not reported as people lack awareness about women rights and considers violence as a domestic right. This paper attempts to provide a deep insight about the causes of physical violence in an intimate relation, its health implications along with possible recommendations to overcome it.